Reflecting on the architecture curriculum through a survey on career switching - Zhao, Shenghuan; Angelis, Enrico De; Ma, Dongqing (Design and Technology Education: An International Journal, 2018)
Due to the deteriorating investment environment, many real-estate companies in China have started transferring their business out of the construction industry. This leads to the shrinkage of the design market and also architects’ salary. A great number of architects have switched career to maintain the same living quality as before. Meanwhile, architectural education in China is not able to integrate itself with emerging science and technologies, losing possibilities to explore new employment channels for its graduates. There is a huge gap between qualities needed in the current or future labour market and the architectural education in schools. An online survey was conducted to investigate the current state of architects’ career shifting, trying to expose the problem mentioned above. In the second part of this paper, education missions from 50 universities are analysed and detailed education curriculums from three top universities are scrutinised. At the end, the education boundary is suggested to be reconstructed from three aspects: integrating the emerging technologies; reducing unnecessary content; and training in self-learning skills.